Gender-Based Differences and Barriers in Skin Protection Behaviors in Melanoma Survivors - Jeffrey Chen; Johnny Shih; Andrew Tran; Aaron Mullane; Christina Thomas; Nail Aydin; Subhasis Misra (Journal of Skin Cancer)
Purpose. Skin protection behaviors and environmental exposure play a crucial role in the development and subsequent management of melanoma. This study investigates gender-based differences in skin protection behaviors after melanoma treatment. Methods. Patients diagnosed and surgically treated for cutaneous melanomas over the last six years in a geographically high risk area were surveyed over telephone using a standardized script. Results. Of 150 survey results obtained, there were 82 males and 68 females. Overall, 87% of participants reported skin self-examination for abnormal markings more often and 94% reported wearing skin protective clothing more often, with females being more than males. Females limited outdoor activity more often than males, 79% to 54%, p<0.05. When outside, females sought shade more often than males, 75% to 56%, p<0.05. However, males wore a wide brim hat more often than females, 52% to 28%, p<0.05. Interestingly, 60% of participants reported wearing SPF 30 sunscreen less often, p<0.05. Conclusion. Larger percentage of females adopted behavioral changes to prevent future melanoma. Those living in high risk areas and with outdoor occupations need particular attention to skin care. Population based screening should be adopted to deal with this rising public health crisis.